Pathogenesis and Immune Response of Ebinur Lake Virus: A Newly Identified Orthobunyavirus That Exhibited Strong Virulence in Mice - Zhao, Lu; Luo, Huanle; Huang, Doudou; Yu, Ping; Dong, Qiannan; Mwaliko, Caroline; Atoni, Evans; Nyaruaba, Raphael; Yuan, Jiangling; Zhang, Guilin; Bente, Dennis; Yuan, Zhiming; et al. (Frontiers in Microbiology, 2021)
Orthobunyaviruses are a group of viruses with significant public and veterinary health importance. These viruses are mainly transmitted through mosquito-, midge-, and tick-vectors, and are endemic to various regions of the world. Ebinur Lake virus (EBIV), a newly identified member of Orthobunyavirus, was isolated from Culex mosquitoes in Northwest China. In the present study, we aimed to characterize the pathogenesis and host immune responses of EBIV in BALB/c mice, as an animal model. Herein, we determined that BALB/c mice are highly susceptible to EBIV infection. The infected mice exhibited evident clinical signs including weight loss, mild encephalitis, and death. High mortality of mice was observed even with inoculation of one plaque-forming unit (PFU) of EBIV, and the infected mice succumbed to death within 5–9 days. After EBIV challenge, rapid viremic dissemination was detected in the peripheral tissues and the central nervous system, with prominent histopathologic changes observed in liver, spleen, thymus, and brain. Blood constituents’ analysis of EBIV infected mice exhibited leukopenia, thrombocytopenia, and significantly elevated ALT, LDH-L, and CK. Further, EBIV infection induced obvious cytokines changes in serum, spleen, and brain in mice. Collectively, our data describe the first study that systematically examines the pathogenesis of EBIV and induced immune response in an immunocompetent standard mouse model, expanding our knowledge of this virus, which may pose a threat to One Health.